Effects of follicular output rate on cumulative clinical pregnancy rate and cumulative live birth rate in PCOS patients with different characteristics - Jiang, Rulan; Cao, Mingya; Hao, Haomeng; Jia, Rui; Chen, Peipei; Liu, Yuanyuan; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Objective We aim to explore the effects of follicular output rate (FORT) on cumulative clinical pregnancy rate (CCPR) and cumulative live birth rate (CLBR) in polycystic ovary syndrome (PCOS) patients with different characteristics undergoing in vitro fertilization (IVF) treatment. Methods This retrospective study analyzed 454 patients with PCOS undergoing their first IVF cycle at our center from January 2016 to December 2020. FORT was calculated as pre-ovulatory follicle count (PFC) × 100/antral follicle count (AFC). Multivariate regression analyses were conducted to explore the relationships between FORT and CCPR and CLBR. Curve fitting and threshold effect analyses were established to find nonlinear relationships. Effect modification in different subgroups were examined by stratification analyses. Results Based on the FORT values, individuals were classified into the following three groups: low-FORT group, middle-FORT group and high-FORT group. Multivariate regression analyses revealed that FORT was an independent factor affecting the CCPR and CLBR significantly (OR = 1.015, 95% CI: 1.001, 1.030 and OR = 1.010, 95% CI:1.001, 1.020). Curve fitting and threshold effect analyses showed that the CCPR and CLBR had a positive correlation with FORT when the FORT was less than 70% (OR = 1.039, 95% CI: 1.013, 1.065 and OR = 1.024, 95% CI: 1.004, 1.044). Stratification analyses showed that the CLBR increased by 1.3% with each additional unit of FORT for patients with hyperandrogenic manifestations (OR = 1.013, 95% CI: 1.001, 1.025). Compared with the low-FORT group, in the high-FORT group, CCPR increased 1.251 times for patients with polycystic ovarian morphology, while CCPR and CLBR increased 1.891 times and 0.99 times for those with ovulation disorder, respectively (OR = 2.251, 95% CI: 1.008, 5.028 and OR = 2.891, 95% CI: 1.332, 6.323 and OR = 1.990, 95% CI: 1.133, 3.494). Conclusion In patients with PCOS, cumulative IVF outcomes have a positive correlation with FORT when the FORT is less than 70%. For PCOS patients with polycystic ovarian morphology, ovulation disorder or hyperandrogenic manifestations, a high FORT could be conductive to achieving better pregnancy outcomes.